Culture and Country towards Child Right in Nepal - Lamsal, Apar Kumar (Researcher: A Research Journal of Culture and Society, 2013)
It has scientifically proved that childhood is the most creative period of human life. It is the basic building block of human development. One of the famous humanitarian personalities of the world, Mahatma Gandhi rightly said "If we are to have real peace, we must begin with the children." It is necessary to make this period safer, creative. But it is worldwide threatening to the children from the terrorism and different kinds of child abuse like child labor, child trafficking, gender discrimination, prohibition from the education etc. Nepal is one of the countries which are not out of them. It is the time for thinking how to safe children. Though Nepal has already formulated laws regarding the child right, but they are only "paper tiger". So, it is necessary to implement the existing laws and abolish the all kind of discrimination and child abuse and follow the international convention relating to child right. DOI: http://dx.doi.org/10.3126/researcher.v1i1.8369 Researcher: A Research Journal of Culture and Society Vol.1(1) 2013